Discourse and Ideology. The Relation Mexico-US regarding the Border Wall - Ahuactzin Martinez, Carlos (2019)
Latin America´s historical migration to North America has es- tablished a deep cultural, economic and political bond between Mexico and US, by means of institutional discursive process in each new North-American government. The candidate Donald Trump proposed the construction of a border wall during his electoral campaign, with the purpose of stopping Mexican migration, drug trafficking and transboundary criminals. In this context, the study analyses the discourse and communicative framework of the border wall, on the basis of Critical Discourse Analysis and the Ideo- logical Studies of Right-Wing Populism. The corpus of the work developed in the Political Communication Laboratory of the Government Sciences and Strategic Development Institute considers two discursive processes: a) Trump´s statements and electoral advertising on TV, and b) Enrique Peña Nieto´s statements on TV. The analysis incorporates the perspective of the multimodal discourse; therefore, audiovisual language is explored in its dimensions. The research questions are the following: how does foreign policy has been conceived with regard to the bilateral relation US-Mexico? And in which way the Mexican citizens are represented in the border wall´s discourse? This qualitative perspective organizes the multi- modal categories in: a) sound, b) visual and c) linguistic levels. Two political dimensions articulate the study: a) the legitimacy of foreign policy and b) citizens´ representation within the discourse. The labeling pro- cess of the corpus incorporates the use of ELAN software, which allows the integration of the analysis levels, conceived in the multimodal discourse com- position. The analysis outcomes establish the ideological discursive lines of both, Mexican and American institutional leaders, and allow an under- standing of the discursive strategies that have established foreign policy in this region of North America.